The Influence of Job Insecurity, Organizational Climate and Work Stress on Turnover Intention of Non-Pns Employees in Sub-District and Sub-District Offices in East Ciputat District - Hamsinah Hamsinah (Peneliti.net, 2018)
This study aims to determine the effect of Job Insecurity, Organizational Climate and Work Stress on Turnover Intention of Non-PNS Employees in District and Kelurahan Offices in East Ciputat District. This study uses primary data obtained from the results of distributing questionnaires. The population used in this study were 168 non-civil servant employees in the District and Kelurahan Offices of East Ciputat District, while the sample used was 118 non-civil servants in the District and Kelurahan Offices of East Ciputat District. The sampling technique used was the Purpose Sampling Method. This research method uses quantitative methods using multiple regression analysis formulas, multiple correlation coefficients, coefficient of determination, t test and f test. Data analysis used parametic statistics with the help of SPSS software. The results of this study indicate that Job Insecurity has a positive and significant effect on Turnover Intention. Organizational climate has a negative and significant effect on Turnover Intention. Job Stress has a positive and significant effect on Turnover Intention. Job Insecurity, Organizational Climate, Work Stress together have a positive and significant effect on Turnover Intention